How to catch a mermaid ebook - Wallace, Adam (How to Catch., 2018)
An enchanting mermaid tale from the New York Times and USA Today bestselling How to Catch series, the perfect Easter basket stuffer for kids! Many claim to have caught a mermaid, but can YOU? Perfect for mermaid lovers, summer reading, and gifts for kids ages 4-10, this funny mermaid picture book offers an irresistible under-the-sea adventure that parents, educators, and children will love! Brimming with fun STEAM-based traps, clever rhymes, and plenty of laughs to share in at-home and classroom read alouds, this magical story makes a perfect stocking stuffer and birthday, Easter, or back to school gift for kids and mermaid lovers alike! How do you catch a mermaid? You must be very clever. With mirrors, crowns, and pearls galore, this quest can't last forever! Also in the How to Catch Series: How to Catch a Unicorn How to Catch a Yeti How to Catch a Dinosaur How to Catch a Dragon How to Catch a Monster and more!